Drug resistance‐related microRNAs in osteosarcoma: Translating basic evidence into therapeutic strategies. Issue 4 (5th February 2019) - Chen, Ruiling; Wang, Gangyang; Zheng, Ying; Hua, Yingqi; Cai, Zhengdong
Abstract: Although the application of multiple chemotherapy brought revolutionary changes to improve overall survival of osteosarcoma patients, the existence of multidrug resistance (MDR) has become a great challenge for successful osteosarcoma treatment in recent decades. Substantial studies have revealed various underlying mechanisms of MDR in cancers. As for osteosarcoma, evidence has highlighted that microRNAs (miRNAs) can mediate in the processes of DNA damage response, apoptosis avoidance, autophagy induction, activation of cancer stem cells, and signal transduction. Besides, these drug resistance‐related miRNAs showed much promise for serving as candidates for predictive biomarkers of poor outcomes and shorter survival time, and therapeutic targets to reverse drug resistance and overcome treatment refractoriness. This review aims to demonstrate the potential molecular mechanisms of miRNAs‐regulated drug resistance in osteosarcoma, and provide insight in translating basic evidence into therapeutic strategies.